APLIKASI SISTEM INFORMASI GEOGRAFIS PADA LOKASI DAN POLA SEBARAN BANGUNAN MUSEUM DI WILAYAH GERBANGKERTOSUSILA - Aliyah, Rahma Annisa (Universitas Negeri Surabaya, 2023)
The Gerbangkertosusila area consists of the urban which have many stories and quite a lot of historical value and leave many historical heritages which are one of the attractions for visitors to visit. History and culture can be found in a place called a museum. However, information on the existence of the museum is less known by visitors. Most visitors only visit a few busy museums because they are easy to find in the city center. This makes the museum which is rarely known to be empty of visitors and will be left behind by the next generation. The purpose of this study was to determine the distribution of museum locations in the Gerbangkertosusila Region using the nearest neighbor analysis method using manual calculations and using the Arcgis software. The results of nearest neighbor analysis using manual calculations show that the distribution pattern of museums in the Gerbangkertosusila Region is categorized as a random distribution pattern, while the results of the distribution pattern in each of the Gerbangkertosusila Regions are broadly categorized as a clustered distribution pattern except for Surabaya City, which is a random distribution pattern. The results of the nearest neighbor analysis using Arcgis software show that the distribution pattern of museums in the Gerbangkertosusila Region is categorized as a clustered distribution pattern, while the results of the distribution pattern in each of the Gerbangkertosusila Regions are broadly categorized as an even distribution pattern except for Surabaya City, which is a random distribution pattern.